2006
DOI: 10.1177/106591290605900310
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Impact of Supreme Court Decisions on Public Opinion: Gay Civil Rights Cases

Abstract: The theoretical and empirical debate over the ability of the U.S. Supreme Court to influence public opinion through its decisions is far from settled. Scholars have examined the question using a variety of theoretical perspectives and empirical evidence, but there is no theoretical consensus, nor are the empirical studies without methodological weaknesses. We enter this debate in an attempt to bring some clarity to the theoretical approaches, overcome some of the methodological shortcomings, and bring a yet un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 62 publications
4
47
1
1
Order By: Relevance
“…Moreover, we did not find an increase in opposition to other LGB rights issues (such as housing or employment protections). Our findings contrast previous research that did show that public opinion on LGB rights became more negative following the Supreme Court ruling that decriminalized same-sex sex (Lawrence v. Texas) (Engel, 2013;Stoutenborough, Haider-Markel, and Allen, 2006). The difference may reflect the extent to which media coverage following the 2015 marriage ruling was more positive than the coverage following the 2003 sodomy ruling insofar as media coverage plays an important role in shaping how the public responds to Supreme Court decisions (Linos & Twist, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, we did not find an increase in opposition to other LGB rights issues (such as housing or employment protections). Our findings contrast previous research that did show that public opinion on LGB rights became more negative following the Supreme Court ruling that decriminalized same-sex sex (Lawrence v. Texas) (Engel, 2013;Stoutenborough, Haider-Markel, and Allen, 2006). The difference may reflect the extent to which media coverage following the 2015 marriage ruling was more positive than the coverage following the 2003 sodomy ruling insofar as media coverage plays an important role in shaping how the public responds to Supreme Court decisions (Linos & Twist, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…This shift may be explained by the fact that there was negative media coverage of the ruling, which included a greater focus on the opinions of those who opposed the ruling, including the dissent by Justice Scalia (HaiderMarkel, 2004;Stoutenborough, Haider-Markel, and Allen, 2006). In addition, scholars argue that the degree to which LGB individuals are sexualized leads to less support of LGB rights (Persily, Egan, and Wallsten, 2006), which may have impacted public opinion following Lawrence v.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several conditions to this relationship. For the Court to shape public opinion, citizens must know about the decision, citizens must trust the Court, and citizens must have weak preferences or be willing to change their opinion (Stoutenborough, Haider-Markel, and Allen 2006). T. R. Johnson and Martin (1998) argue that landmark cases provide the best opportunity for a Court decision to shape opinion, however, under certain conditions, a reversal on a previous Court decision may also result in significant shifts in opinion.…”
Section: Can Policy Create New Social Norms Via Signaling?mentioning
confidence: 99%
“…Several studies have demonstrated the number of ways in which courts may influence public opinion and support (see, e.g., Clawson et al , Franklin and Kosaki , Gibson and Caldeira , Grosskopf and Mondak , Hoekstra and Segal , Johnson and Martin , Mondak, , , , Stoutenborough et al ). According to this literature, court decisions, particularly on issues of national interest, may have an impact on public opinion, which can manifest itself either as increased support or increased opposition to the position taken by the court.…”
Section: Judicial Dissent and Public Support For Court Decisionsmentioning
confidence: 99%